Mini review: The role of sensory innervation to subchondral bone in osteoarthritis pain - Morgan, Michael; Nazemian, Vida; Harrington, Kate; Ivanusic, Jason J. (Frontiers in Endocrinology, 2022)
Osteoarthritis pain is often thought of as a pain driven by nerves that innervate the soft tissues of the joint, but there is emerging evidence for a role for nerves that innervate the underlying bone. In this mini review we provide evidence that subchondral bone lesions are associated with pain in osteoarthritis. We explore recent studies that provide evidence that sensory neurons that innervate bone are nociceptors that signal pain and can be sensitized in osteoarthritis. Finally, we describe neuronal remodeling of sensory and sympathetic nerves in bone and discuss how these processes can contribute to osteoarthritis pain.